Koneksi Politik dan Penghindaran Pajak pada Perusahaan Sektor Pertambangan dan Konstruksi - Mahardika, Tiska Ayu; Sucahyati, Diarany (Forum Kerjasama Pendidikan Tinggi, 2025)
Tax avoidance is a central issue in optimizing state revenue. The mining and construction sectors in Indonesia are highly vulnerable to tax avoidance due to complex business structures and involvement in government projects. This study aims to examine the effect of political connections on tax avoidance in mining and construction companies listed on the Indonesia Stock Exchange during the 2019–2023 period. Political connections are identified based on the presence of Politically Exposed Persons (PEPs) on the board of commissioners or directors. Tax avoidance is measured using the ratio of income tax expense to profit before tax, known as the Effective Tax Rate (ETR). A total of 418 observations were selected using purposive sampling. The data were analyzed using panel data regression with control variables, processed through STATA 17.0 software. The results reveal that political connections have a positive and statistically significant effect on ETR, with a coefficient of 0.090 at the 10% significance level. This indicates that companies with political connections tend to exhibit higher tax compliance compared to those without such connections. These findings support the notion that political connections can enhance corporate fiscal oversight and accountability rather than encourage tax avoidance.